The role of gender and personality (Type "A" and "B"); on emotional stressful experience - Ofojebe Chukwuma Philip; Okoli Paul Chibuike; Okpala Micheal Okemefuna (Annals of Alzheimer's and Dementia Care - Peertechz Publications, 2019)
Background: Stress is not merely something that makes one worry. It is rather ubiquitous. It is synonymous with life. We live in an age of great stress and anxiety and it impacts more on our life and social wellbeing depending on one's gender and personality types. Aim: To increase our knowledge of the role of stress in human life, social, and physical wellbeing and to create awareness on the harmful effect of the clinical condition of stress. Setting: The study was carried out teachers in 18 public Secondary schools in Aguata and Anaocha Local Government Councils of Anambra State Nigeria. Method: This was a cross-sectional and descriptive study of 90 secondary school teachers using Jenkins Activity Survey Scale (Jas), Symptom Distress Checklist (Scl-90) and a sociodemographic questionnaire. Results: On the role of gender and personality types on emotional stressful experience, a personality has the highest mean of 120.24; while type B personality has the total mean of 96.96 while on gender scale, the females have the mean of 109.67 and males have the mean of 107.13. Conclusion: Personality Type as a factor yielded a significant effect in manifestation of emotional stress. Gender however did not significantly affect manifestation of emotional stress. On the other hand it was shown that there is interactive effect between gender and personality type in emotional stress reaction to noxious life experiences.